Energetics of substrate transport in proton-dependent oligopeptide transporters - Balaji Selvam; Nicole Chiang; Diwakar Shukla (Communications Chemistry)
Abstract The PepTSo transporter mediates the transport of peptides across biological membranes. Despite advancements in structural biology, including cryogenic electron microscopy structures resolving PepTSo in different states, the molecular basis of peptide recognition and transport by PepTSo is not fully elucidated. In this study, we used molecular dynamics simulations, Markov State Models (MSMs), and Transition Path Theory (TPT) to investigate the transport mechanism of an alanine-alanine peptide (Ala-Ala) through the PepTSo transporter. Our simulations revealed conformational changes and key intermediate states involved in peptide translocation. We observed that the presence of the Ala-Ala peptide substrate lowers the free energy barriers associated with transition to the inward-facing state. We also show a proton transport model and analyzed the pharmacophore features of intermediate states, providing insights for rational drug design. These findings highlight the significance of substrate binding in modulating the conformational dynamics of PepTSo and identify critical residues that facilitate transport.